2021
DOI: 10.1016/s2468-2667(21)00097-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smoke-free policies in outdoor areas and private places on children's tobacco smoke exposure and respiratory health: a systematic review and meta-analysis

Abstract: Background Smoke-free policies in outdoor areas and semi-private and private places (eg, cars) might reduce the health harms caused by tobacco smoke exposure (TSE). We aimed to investigate the effect of smoke-free policies covering outdoor areas or semi-private and private places on TSE and respiratory health in children, to inform policy. MethodsIn this systematic review and meta-analysis, we searched 13 electronic databases from date of inception to Jan 29, 2021, for published studies that assessed the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…Smoke Free Area regulation is one of the government’s efforts to control diseases caused by smoking and exposure to cigarette smoke in the environment. A meta-analysis research shows that smoke free area regulation as implementation of WHO’s recommended tobacco control policies (MPOWER) was associated with substantial benefits to health especially on perinatal and children health, especially who got in tobacco smoke exposure [ 13 , 14 ]. The WHO MPOWER recommendation were able to reduce the adult daily smoking prevalence significantly the countries with higher initial tobacco control preparedness and higher smoking burden [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Smoke Free Area regulation is one of the government’s efforts to control diseases caused by smoking and exposure to cigarette smoke in the environment. A meta-analysis research shows that smoke free area regulation as implementation of WHO’s recommended tobacco control policies (MPOWER) was associated with substantial benefits to health especially on perinatal and children health, especially who got in tobacco smoke exposure [ 13 , 14 ]. The WHO MPOWER recommendation were able to reduce the adult daily smoking prevalence significantly the countries with higher initial tobacco control preparedness and higher smoking burden [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Protecting children from the harmful effects of tobacco smoke exposure is essential and regulating smoking in cars is important given the extremely high levels of toxins. Alongside existing studies showing that these measures can reduce tobacco smoke exposure inside cars, 8 the Scottish study provides further impetus to accelerate implementation of similar policies across the globe. Such policies should be part of a comprehensive approach to tobacco control, which includes smoke-free policies covering public places and workplaces if not already in place.…”
Section: Protecting Children From Tobacco-related Harm In Private Vehiclesmentioning
confidence: 98%
“…Márta Radó and colleagues' systematic review identified five quasi-experimental studies on the links between smoke-free car policies and children's tobacco smoke exposure, with only one study reporting health outcomes. 8 Meta-analysis of ten estimates from four of these studies found an immediate 31% (95% CI 13-45) reduction in children's tobacco smoke exposure inside vehicles, but the low number of studies precluded examination of subgroup effects, and there was little consideration of links with hard clinical outcomes in individual studies. Mackay and colleagues 6 address these gaps in the evidence base.…”
Section: Protecting Children From Tobacco-related Harm In Private Vehiclesmentioning
confidence: 99%
“…The prevalence of SHS exposure among women in reproductive age (15–49 years) in Egypt is estimated to be 65% [ 11 ], and about 50% of pregnant non-smoking women in Egypt are exposed daily to SHS [ 12 ] compared to 29% of non-smoking adults in European Union [ 13 ]. Pervious evidence reported significant relation between SHS exposure reductions on public places as school and in private places as cars and lower hospital admissions due to respiratory illness among children, following a comprehensive smoke-free policy [ 14 ]. In 2014, 35% of Egyptian school students (aged 13–15) were exposed to SHS at home and 55% in enclosed public places [ 15 ].…”
Section: Introductionmentioning
confidence: 99%